Personalized Web Search Using Browsing History and Domain Knowledge Based on Enhanced User Profile - Gajul Rohit (Journal of Telematics and Informatics, 2015)
Generic search engines are important for retrieving relevant information from web. However these engines follow the "one size fits all" model which is not adaptable to individual users. Personalized web search is an important field for tuning the traditional IR system for focused information retrieval. This paper is an attempt to improve personalized web search. User's Profile provides an important input for performing personalized web search. This paper proposes a framework for constructing an Enhanced User Profile by using user's browsing history and enriching it using domain knowledge. This Enhanced User Profile can be used for improving the performance of personalized web search. In this paper we have used the Enhanced User Profile specifically for suggesting relevant pages to the user. The experimental results show that the suggestions provided to the user using Enhanced User Profile ae better than those obtained by using a User Profile.